A Radiocarbon‐Based Framework to Assess Soil Organic Carbon Persistence and Vulnerability Across Land‐Use Types - Luisa I. Minich; Jeffrey Beem‐Miller; Benedict V. A. Mittelbach; Dylan Geissbühler; Annegret Udke; Daniel Wasner; Margaux Moreno Duborgel; Ciriaco McMackin; Alexander S. Brunmayr; Lukas Wacker; Philip Gautschi; Negar Haghipour; et al. (Global Change Biology, 2026)
Soil organic carbon (SOC) can persist from days to millennia but remains vulnerable to carbon (C) loss upon disturbances, depending on environmental conditions and mode of stabilization. Understanding drivers of persistence and vulnerability is crucial to assess soil C sequestration as well as potential SOC losses due to changes in climate and land use. Here, we investigate SOC persistence and vulnerability in five land‐use types by combining radiocarbon‐derived estimates of SOC age (system age) and age of respired CO 2 (transit time) with indicators of biological (SOC decomposability) and thermal stability (residual oxidisable carbon content, ROC). Based on this, we developed a vulnerability index for SOC and applied it across soil profiles from 19 sites representing temperate and alpine grasslands, forests, croplands, and managed peatlands. Transit times and system ages ranged from 2 years in the organic layer of forests to 5760 years in subsoils of managed peatlands and varied significantly across land‐use types and soil depth. Transit times were generally shorter than system ages, indicating that soil‐respired CO 2 is dominated by more recent inputs, while bulk SOC contains more persistent C. In forests, temperate grasslands, and croplands, system ages were positively linked to thermal stability and mineral reactivity, indicating higher SOC persistence through organo‐mineral stabilization. In contrast, alpine grasslands and managed peatlands showed centennial to millennial system ages despite low thermal stability ( 90 kg m −2 in managed peatlands), this implies a high vulnerability of these soils to environmental disturbances that alleviate these constraints. Our findings demonstrate that combining metrics of biological and thermal stability with radiocarbon data provides a powerful framework to assess SOC vulnerability to disturbances induced by environmental change.

Low organic carbon storage of sediment due to frequent river course changes in Yellow River Delta - Dongxue Li; Zhonghua Ning; Kristof Van Oost; Wasner Daniel; Yi’na Li; Baoshan Cui; Sebastian Doetterl (CATENA, 2025)

Quantity Versus Quality: Links Between Soil Organic Matter and Bacterial Community Composition Along a Geoclimatic Gradient - Daniel Wasner; Xingguo Han; Joerg Schnecker; Aline Frossard; Erick Zagal Venegas; Sebastian Doetterl (Environmental Microbiology, 2025)
Soil organic matter (SOM) quantity drives soil bacterial community composition from the regional to global scale. Qualitative characteristics of SOM are known to affect soil bacterial communities in manipulation experiments. However, it remains unresolved how strongly SOM characteristics affect soil bacterial community composition at the macroscale. Here, we investigated how quantity versus qualitative characteristics of SOM shape community composition along a biogeochemical gradient of grassland soils. We assessed relative abundance patterns of soil bacteria and characterised SOM based on scalable methods. Soils with higher SOM content (along a continuum between 0.6% and 18.7% SOC) and acidic pH (along a continuum between pH 4.1–6.7) hosted fewer narrowly distributed taxa (i.e., taxa occurring in few sites) and therefore had lower bacterial alpha diversity. We could explain a larger fraction of bacterial community composition (up to 59.6% of 16S rRNA reads) in these soils. Consequently, we understand community composition in low‐SOM soils less than in high‐SOM soils, because the drivers of narrowly distributed taxa remain poorly understood. Qualitative SOM characteristics did not strongly affect biogeographical patterns of widely distributed soil bacterial taxa. This suggests that broad aspects of SOM quality do not dominate soil bacterial community composition at the investigated macroscale.

Diversity and functionality of soil prokaryotic communities in antarctic volcanic soils: insights from penguin-influenced environments - Diego Segura; Karen Jordaan; Beatriz Díez; Javier Tamayo-Leiva; Sebastian Doetterl; Daniel Wasner; Jerónimo Cifuentes-Anticevic; Angélica Casanova-Katny (Polar Biology, 2024)

Environment and microbiome drive different microbial traits and functions in the macroscale soil organic carbon cycle - Daniel Wasner; Joerg Schnecker; Xingguo Han; Yifei Sun; Aline Frossard; Erick Zagal Venegas; Pascal Boeckx; Sebastian Doetterl (Global Change Biology, 2024)
Soil microbial traits and functions play a central role in soil organic carbon (SOC) dynamics. However, at the macroscale (regional to global) it is still unresolved whether (i) specific environmental attributes (e.g., climate, geology, soil types) or (ii) microbial community composition drive key microbial traits and functions directly. To address this knowledge gap, we used 33 grassland topsoils (0–10 cm) from a geoclimatic gradient in Chile. First, we incubated the soils for 1 week in favorable standardized conditions and quantified a wide range of soil microbial traits and functions such as microbial biomass carbon (MBC), enzyme kinetics, microbial respiration, growth rates as well as carbon use efficiency (CUE). Second, we characterized climatic and physicochemical properties as well as bacterial and fungal community composition of the soils. We then applied regression analysis to investigate how strongly the measured microbial traits and functions were linked with the environmental setting versus microbial community composition. We show that environmental attributes (predominantly the amount of soil organic matter) determined patterns of MBC along the gradient, which in turn explained microbial respiration and growth rates. However, respiration and growth normalized for MBC (i.e., specific respiration and growth) were more linked to microbial community composition than environmental attributes. Notably, both specific respiration and growth followed distinct trends and were related to different parts of the microbial community, which in turn resulted in strong effects on microbial CUE. We conclude that even at the macroscale, CUE is the result of physiologically decoupled aspects of microbial metabolism, which in turn is partially determined by microbial community composition. The environmental setting and microbial community composition affect different microbial traits and functions, and therefore both factors need to be considered in the context of macroscale SOC dynamics.

Global prediction of soil microbial growth rates and carbon use efficiency based on the metabolic theory of ecology - Decai Gao; Edith Bai; Daniel Wasner; Frank Hagedorn (Soil Biology and Biochemistry, 2024)

Predicting Soil Organic Carbon Mineralization Rates Using δ13C, Assessed by Near-Infrared Spectroscopy, in Depth Profiles Under Permanent Grassland Along a Latitudinal Transect in Chile - Hidalgo Marcela; María de los Ángeles Sepulveda; Cristina Muñoz; Manuel Casanova; Daniel Wasner; Samuel Bodé; Sebastian Doetterl; Pascal Boeckx; Erick Zagal (Journal of Soil Science and Plant Nutrition, 2022)

Soil Nutrient Depletion and Tree Functional Composition Shift Following Repeated Clearing in Secondary Forests of the Congo Basin - Marijn Bauters; Pieter Moonen; Laura Summerauer; Sebastian Doetterl; Daniel Wasner; Marco Griepentrog; Francis M. Mumbanza; Elizabeth Kearsley; Corneille Ewango; Faustin Boyemba; Johan Six; Bart Muys; et al. (Ecosystems, 2021)